Effects of oral administration of caffeine on some physiological parameters and maternal behaviour of sows at farrowing. (April 2016) - Superchi, Paola; Saleri, Roberta; Farina, Elena; Cavalli, Valeria; Riccardi, Enzo; Sabbioni, Alberto
Abstract: Caffeine has been demonstrated to have a protective effect on neonatal viability of piglets. In order to assess whether caffeine, administered to parturient sows, also affects maternal behaviour, respiratory rate, and dopamine, nitric oxide and serotonin plasma levels, 20 sows, with induced parturition, received orally 27 mg/kg of body weight of caffeine (T group; n  = 10) or not (NT group; n  = 10), on day 113 of gestation. Treatment did not affect the farrowing length. There were less stillborn piglets in T group than NT group (0.67 vs 2.44; P  < 0.05), whereas no differences in dead piglets at 24 h from birth was observed. Caffeine did not affect physiological parameters of sows, as the behaviour score of sows laying on belly was reduced ( P  < 0.05). In conclusion, although the present study was carried out with a limited number of sows, administration of caffeine to parturient sows has the potential for reducing the number of stillborn. Highlights: Caffeine orally administered to parturient sows. Caffeine does not cause behavioural changes in farrowing sows. Caffeine does not affect plasma levels of neurotransmitters of farrowing sows. Caffeine reduces stillbirth rate.